Experiences of LGBTQ student-athletes in college sports: a meta-ethnography - Xiang, Meng; Soh, Kim Geok; Xu, Yingying; Ahrari, Seyedali; Zakaria, Noor Syamilah (Elsevier, 2023)
This study aimed to explore and describe the experiences of LGBTQ student-athletes to identify ways in which athletic staff, coaches, and others can support LGBTQ youth's safe participation in sports. Guided by the preferred reporting items for systematic reviews (PRISMA) and eMERGe reporting guidance. We conducted a meta-ethnography to synthesize qualitative research focused on student-athletes’ experiences. Fourteen studies were included in the meta-ethnography published between 1973 and 2022. Four themes were identified: (1) experiences of discrimination and violence; (2) perceived stigma; (3) internalized prejudice; and (4) coping and team support, and they were used to generate a line of argument model, which explains the stress process of LGBTQ student-athletes in the sports. LGBTQ student-athletes experience persistent discrimination in college sports, which poses a significant risk to their mental health. Meanwhile, this study identified that qualitative research on LGBTQ youth sports participation is lacking in many regions of the world and lacks knowledge of the sports participation experience of bisexual, gay, and transgender students. These findings revealed a way for research on LGBTQ-related issues and future policy and practice on LGBTQ youth-related issues in sports.